ACCOUNTING IN THE ENGINEERING CURRICULUM. - Stevenson, R. A. (The Accounting Review, 1930)
Abstract Accounting has been offered in some form to students in engineering schools for at least twenty years. It is only recently, however, that serious consideration has been given to this subject as an integral part of the required curriculum. The fact that engineers were entering positions of administrative responsibility in which their technical training was not directly applied, brought to the attention of engineering faculties the need for some adjustment in their established curricula. The collegiate Schools of Business started their phenomenal growth about the same time as the movement for industrial management in engineering and largely for the same reason. The first call for business training came from concerns that needed trained accountants and cost analysts. Somewhat later, the schools of business began to give more attention to the fields of marketing and finance which at present occupy a considerable part of their attention. The accounting courses in engineering should be a part of a management training program fitted into an adjustment of the curriculum of the existing courses in mechanical, electrical, civil and chemical engineering.